Gestão escolar: desafios e possibilidades da gestão participativa na escola pública - Alves, Márcia Galdino (2017)
The purpose of this research was to investigate the role of the public school director, who is concerned with the construction of a school management that promotes the participation of teachers, students, parents and employees in decision making and public school actions. In a scenario of rapid social, economic and scientific technical transformations, the school must take a serious commitment to the continuous training of the professionals who work in it, because at school these transformations trigger new opportunities and challenges. The principal has an important pedagogical role as mediator of the educational process and must lead this training process by providing spaces for continuing education. Based on the work of Libâneo (2004), this research investigated, through cooperative action research, participatory management and its relationship with continuing education. Data were collected through a Reflection Group, questionnaire survey and document analysis. In an unfavorable school context for the implementation of participatory management, the continuous formation, through the constitution of a reflective group, showed that a participatory environment can be stimulated and, thus, lead the school to a new management model, based on the Active participation of its team. The five training meetings were held from May to June 2017 and the theme chosen by the reflective group, comprised of seven teachers from a municipal public school, was school indiscipline. The meetings provoked important discussions and resulted in a plan of action collectively planned to respond to the problem of indiscipline of the school unit